Pharmacogenomics. Issue 10197 (10th August 2019) - Roden, Dan M; McLeod, Howard L; Relling, Mary V; Williams, Marc S; Mensah, George A; Peterson, Josh F; Van Driest, Sara L
Summary: Genomic medicine, which uses DNA variation to individualise and improve human health, is the subject of this Series of papers. The idea that genetic variation can be used to individualise drug therapy—the topic addressed here—is often viewed as within reach for genomic medicine. We have reviewed general mechanisms underlying variability in drug action, the role of genetic variation in mediating beneficial and adverse effects through variable drug concentrations (pharmacokinetics) and drug actions (pharmacodynamics), available data from clinical trials, and ongoing efforts to implement pharmacogenetics in clinical practice.